DOES ERGONOMICS AUGMENT EMPLOYEE INVOLVEMENT AMONG THE EMPLOYEES OF IT SECTOR: AN EMPERICAL STUDY - P.N, Monnappa.; Menon, Rethy (International Journal of Psychosocial Rehabilitation, 2020)
In the present period, the idea of ergonomics has become the need of every work place. Ergonomics plays important role in the organization. Ergonomics is offering an environment that facilitates best to the employee’s performance in overall productivity of the organization. Employees are the one of the most important asset for any organization. Ergonomics helps to solve the problems related to organizational work stress in the job environment, occupational health and safety problems, and low efficiency level and job issues. Ergonomic is the technology used to align activities and the environment with the employee’s skill and need to improve performance and improve health and safety. The continuous work in the organization cannot be monitored by employees and their ability of muscle may be limit to sustain contraction and physical fatigue. Ergonomists and other researchers had studied the effects of several work factors on performance including the rate of work and amount of duration of work and the effects of design proper pattern of ergonomic. The main objective of the study was to find out the level of ergonomic activity based on employee performance and the involvement of employees in the IT sectors. Two standardizedquestionnaire were used to gather data from 100 IT employees. The statistical method used in the research included descriptive statistics, t-testing, and correlation. The study found positive association to occur.